STM-induced ring closure of vinylheptafulvene molecular dipole switches on Au(111) - Au-Yeung, Kwan Ho; Kuehne, Tim; Aiboudi, Oumaima; Sarkar, Suchetana; Guskova, Olga; Ryndyk, Dmitry A.; Heine, Thomas; Lissel, Franziska; Moresco, Francesca (Nanoscale Advances, 2022)
Dihydroazulene/vinylheptafulvene pairs are known as molecular dipole switches that undergo a ring-opening/-closure reaction by UV irradiation or thermal excitation. Herein, we show that the ring-closure reaction of a single vinylheptafulvene adsorbed on the Au(111) surface can be induced by voltage pulses from the tip of a scanning tunneling microscope. This cyclization is accompanied by the elimination of HCN, as confirmed by simulations. When inducing lateral movements by applying voltage pulses with the STM tip, we observe that the response of the single molecules changes with the ring closing reaction. This behaviour is discussed by comparing the dipole moment and the charge distribution of the open and closed forms on the surface.
CRIS-Team Scopus Importer:2023-03-20